Molecular Mapping and Analysis of an Excellent Quantitative Trait Loci Conferring Adult-Plant Resistance to Stripe Rust in Chinese Wheat Landrace Gaoxianguangtoumai - Wang, Yuqi; Liang, Fengying; Guan, Fangnian; Yao, Fangjie; Long, Li; Zhao, Xuyang; Duan, Luyao; Wu, Yu; Li, Hao; Li, Wei; Jiang, Qiantao; Wei, Yuming; et al. (Frontiers in Plant Science, 2021)
The Chinese wheat landrace “Gaoxianguangtoumai” (GX) has exhibited a high level of adult-plant resistance (APR) to stripe rust in the field for more than a decade. To reveal the genetic background for APR to stripe rust in GX, a set of 249 F6:8 (F6, F7, and F8) recombinant inbred lines (RILs) was developed from a cross between GX and the susceptible cultivar “Taichung 29.” The parents and RILs were evaluated for disease severity at the adult-plant stage in the field by artificial inoculation with the currently predominant Chinese Puccinia striiformis f. sp. tritici races during three cropping seasons and genotyped using the Wheat 55K single-nucleotide polymorphism (SNP) array to construct a genetic map with 1,871 SNP markers finally. Two stable APR quantitative trait loci (QTL), QYr.GX-2AS and QYr.GX-7DS in GX, were detected on chromosomes 2AS and 7DS, which explained 15.5–27.0% and 11.5–13.5% of the total phenotypic variation, respectively. Compared with published Yr genes and QTL, QYr.GX-7DS and Yr18 may be the same, whereas QYr.GX-2AS is likely to be novel. Haplotype analysis revealed that QYr.GX-2AS is likely to be rare which presents in 5.3% of the 325 surveyed Chinese wheat landraces. By analyzing a heterogeneous inbred family (HIF) population from a residual heterozygous plant in an F8 generation of RIL, QYr.GX-2AS was further flanked by KP2A_36.85 and KP2A_38.22 with a physical distance of about 1.37Mb and co-segregated with the KP2A_37.09. Furthermore, three tightly linked Kompetitive allele-specific PCR (KASP) markers were highly polymorphic among 109 Chinese wheat cultivars. The results of this study can be used in wheat breeding for improving resistance to stripe rust.